Cerebrotendinous xanthomatosis - The spectrum of imaging findings - Pudhiavan, Arunachalam (EduRad, 2013)
Cerebrotendinous xanthomatosis (CTX), also known as Van Bogaert-Scherer-Epstein disease is a rare autosomal recessive genetic disorder of the lipid metabolism. To date, there are less than 300 cases reported worldwide. We present a case of a 30 year old male who presented with mental retardation and swelling of ankles, with the a spectrum of CTX imaging findings. Imaging studies were performed which included plain X-ray, Ultrasound(US) and Magnetic Resonance Imaging(MRI) of both the brain and ankles. These pointed towards the diagnosis of CTX with the entire spectrum of findings which was confirmed with biopsy and laboratory findings. CTX is a potentially treatable condition with replacement therapy, and hence early diagnosis before neurological deterioration is important. This is aided by the imaging findings which are conclusive forte diagnosis of CTX.